2019
DOI: 10.1093/ajcn/nqz218
|View full text |Cite
|
Sign up to set email alerts
|

Detailed 3-dimensional body shape features predict body composition, blood metabolites, and functional strength: the Shape Up! studies

Abstract: Background Three-dimensional optical (3DO) body scanning has been proposed for automatic anthropometry. However, conventional measurements fail to capture detailed body shape. More sophisticated shape features could better indicate health status. Objectives The objectives were to predict DXA total and regional body composition, serum lipid and diabetes markers, and functional strength from 3DO body scans using statistical sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
129
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 77 publications
(136 citation statements)
references
References 26 publications
7
129
0
Order By: Relevance
“…In contrast, the approach used in our study has been shown to identify differences in scale-invariant shape features that cannot be captured using traditional anthropometric techniques. There have been recent studies which have also used principal components analysis (PCA) to detect variations in torso 3D scan data similar to our study, such as Ruto et al 43 and Ng et al 44 . However, the torso scan data in both these investigations were not scaled to uniform size, so as a result some variations observed within these studies were related to differences in overall body height and size, as well as variations in scale-invariant body shape.…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, the approach used in our study has been shown to identify differences in scale-invariant shape features that cannot be captured using traditional anthropometric techniques. There have been recent studies which have also used principal components analysis (PCA) to detect variations in torso 3D scan data similar to our study, such as Ruto et al 43 and Ng et al 44 . However, the torso scan data in both these investigations were not scaled to uniform size, so as a result some variations observed within these studies were related to differences in overall body height and size, as well as variations in scale-invariant body shape.…”
Section: Discussionsupporting
confidence: 59%
“…This proof-of-concept investigation identified and validated a novel 3DO body fat prediction equation that accounts for divergent anthropometric characteristics. The combined equation was found to have acceptable validity and minimal group-level error compared to DXA, mirroring the results of Ng and colleagues, 1 who reported comparable validity of a 3DO-derived prediction equation relative to DXA fat mass estimates in a multi-ethnic, mixed-sex cohort. Taken together, these findings suggest that device-specific 3DO BF% prediction equations could serve as a suitable alternative to DXA to estimate body composition in groups of healthy individuals.…”
supporting
confidence: 77%
“…In recent years, the use of commercially available 3-dimensional optical imaging (3DO) devices has garnered considerable interest as a potentially useful, non-invasive method to evaluate automated anthropometry and body composition for adults 1 , 2 and children. 3 These devices utilize infrared and visible light to create a 3-dimensional representation of a subject’s body, allowing for rapid, automatic assessment of anthropometric characteristics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the potential use of multiple measures for a more precise prediction of body composition, previous studies only considered a limited number of predefined measures [42], and only few of them used automatic variable selection procedures to identify the best predictors [43][44][45]. Because some of the 150 standard measurements are strongly correlated among each other, model selection procedures and other techniques such as 3D surface geometry may have to account for these correlations [46][47][48][49][50][51]. Still, further research is needed to identify which of the 150 standard measurements are most relevant for the prediction of body composition, or whether multiple (and partly strongly correlated) measurements are relevant, and how they should be selected or combined to obtain the most reliable predictions.…”
Section: Introductionmentioning
confidence: 99%